Development of the Prediction System of Condensation Based on Wireless Communications. (11th September 2013) - Choi, Shin-Hyeong
Due to advances in microelectromechanical system (MEMS), many smart sensors have been developed. A large number of sensors build a wireless sensor network and can communicate with each other. Wireless sensor networks help monitor objects in our environment, and many researches about this technology are in progress. Condensation is a phenomenon that water vapor contained in the air condenses and makes water droplets. This is caused by the complex action of a variety of factors, including the temperature difference between indoor and outdoor and excessive indoor moisture, so it is never easy to identify the cause and establish measures for the actual building. In this paper, a system is presented to predict and alert condensation promptly and accurately, considering the causes and prevention of condensation. In this paper, a system will be developed to collect and monitor environmental information causing condensation, in real time using a wireless sensor network in order to build a system to prevent condensation. The users are expected to use this system to easily identify the cause of condensation and take actions based on the cause-specific alarm messages in order to alleviate aesthetics and hygiene problems due to condensation.